2013
DOI: 10.21660/2013.9.3k
|View full text |Cite
|
Sign up to set email alerts
|

Bearing Capacity and Settlement of Footings in Unsaturated Sand

Abstract: ABSTRACT:The focus of the study in this paper is directed towards understanding the influence of three parameters; namely, (i) matric suction, (ii) overburden stress, and (iii) dilation, on the bearing capacity and settlement behavior of surface and embedded model footings in unsaturated sands. The results show that the bearing capacity and settlement behavior of unsaturated sands are significantly influenced by all the three parameters. In addition, comparisons are provided between the predicted and measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…However, the effect of dilation is negligible at higher confining stress (i.e., (s 3 2u a )5200 kPa). These results are consistent with the observations of other investigators in the literature (Zhan, 2003;Vanapalli and Mohamed, 2013).…”
Section: Comparison Between the Experimental And Predicted Values Of supporting
confidence: 94%
See 1 more Smart Citation
“…However, the effect of dilation is negligible at higher confining stress (i.e., (s 3 2u a )5200 kPa). These results are consistent with the observations of other investigators in the literature (Zhan, 2003;Vanapalli and Mohamed, 2013).…”
Section: Comparison Between the Experimental And Predicted Values Of supporting
confidence: 94%
“…More widely, it is used in the calculation of the soil stresses and deformation behavior (Davis and Poulos, 1968;Schmertmann, 1970;Schmertmann et al, 1978;Bowles, 1987;Lade and Nelson, 1987;Lade, 1988;Berardi and Lancellotta, 1991;Lancelotta, 1995;Terzaghi et al, 1996;Mayne and Poulos, 1999;Lee et al, 2008;Akbas and Kulhawy, 2009;Oh et al, 2009;Vanapalli and Mohamed, 2013). Terzaghi's (1925Terzaghi's ( , 1926Terzaghi's ( , 1931 pioneering modeling and experimental studies showed that the swelling and shrinkage characteristics of clay are essentially elastic deformations caused by the clay's affinity for water.…”
Section: Introductionmentioning
confidence: 99%
“…Also, results of CPTs conducted by Vanapoli & Fathi [10] in a specially designed tank showed that cone resistance and bearing capacity of sand can be influenced by suction. Russell and Khalili [11] also showed that the cone penetration resistance is comparable to the required pressure for expansion of a spherical cavity in an infinite sand, and it could be increased due to presence of suction in an unsaturated condition.…”
Section: Introductionmentioning
confidence: 98%
“…Footings with short open-and close-end stumps were experimented by Chan [14] for settlement reduction in soft clay soils as an economical solution to excessive and non-uniform subsidence problems in waterlogged, low-lying areas. Also, Vanapalli& Mohamed [15] and AlKhuzaei [16] the former in a geogrid-reinforced sand bed. No observation was made of the effect of the geogrid base on the overall performance of the footings though.…”
Section: Introductionmentioning
confidence: 99%